What does wellbeing mean to young people and how does this relate to policy discourses? A study of teenagers in one secondary school in Scotland - Stones, Tina Ann (The University of Edinburgh, 2019)
Since the turn of the 21st century there has been a prolific interest in the wellbeing of children and young people globally, nationally and regionally. The interested parties have ranged from politicians, academics, educators and third sector organisations. The sometimes emotionally charged concern of the interested parties has resulted in education being given a greater responsibility for improving the wellbeing of children and young people. A plethora of interventions have been created and implemented to solve the ‘problem’ of childhood fragility, whilst the United Kingdom has experienced severe cuts to children’s services. This study explored what wellbeing means to young people in one secondary school and how this relates to policy discourses on wellbeing. The literature review provided insights into the research practices carried out in the area of wellbeing and schools and showed the different levels of participation in the chosen methods. Child centred practices emerged from the United Nations Convention on the Rights of the Child (1992) and participatory approaches with young people in schools have been embedded to various levels of authenticity in the research studies included in the review. The study illustrates the complexity of the wellbeing agenda and the need for policy making and research practices to be more authentically participatory in nature. Following analysis of the discourses on wellbeing evident in key education policies such as Getting it Right for Every Child and Curriculum for Excellence, the case study design used a thematic analysis to explore how sixteen young people in one secondary school in Scotland understand the term ‘wellbeing’. Young people firstly completed a creative task and then participated in four focus groups to explore their interpretation of the term ‘wellbeing’, specifically the eight wellbeing indicators of ‘Safe; Healthy; Achieving; Nurtured; Active; Respected; Responsible; Included’. The participants were selected from the S1 and S2 cohort in one rural secondary school in the north of Scotland (mean age 12 years and one month in S1 and 13 years in S2). Eight females and eight males participated in the single sex focus groups. The study aimed to gain an insight into the participants’ understanding of wellbeing and to explore how this compared to the definitions used in the Scottish policy context. The policy analysis highlighted the complexity of the definitions used in the Scottish policy context and illustrated how the term ‘wellbeing’ is often ambiguous and interpreted in multifaceted ways, sometimes in one context. The study demonstrated that the young people participating in the focus groups and creative task were fully able to contribute to, and participate in, conversations with their peers which illustrated their understanding of the holistic term ‘wellbeing’. The data analysis revealed that young people in this study referred to a multi-faceted definition of wellbeing with a strong focus on love and trust. Suggestions for the implications flowing from my research data include that the contrasting narratives located in the policy discourses need to be critiqued more deeply to ensure that schools and other educational establishments are making the right choices for those they aim to serve. This could be explored more deeply in specific contexts through working in a participatory manner with those the wellbeing agenda impacts on, facilitating opportunities to capture minority voices.
Keywords: wellbeing; United Nations Convention on the Rights of the Child; wellbeing agenda; education policies; Scottish policy context; young people; school policy